The Correlation of The Knowledge About Menopause With The Readiness Ahead of Menopause For Pre-menopause Women - Agus Eka Nurma Yunita (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Introduction: In this globalisation era, healthiness becomes a precious thing, especially on reproduction health that becomes worldwide attention. Statistics Indonesia (Badan Pusat Statistik (BPS) stated 15,2% of 118 million women in Indonesia has entered the menopause period. According to the beginning survey of 10 premenopausal women, only 2 women knew menopause symptoms signs.Purpose: To analyze the correlation of the knowledge about menopause with the readiness ahead of menopause for premenopausal women.Subject and Method: The research was quantitative analytics with a cross-sectional design. The research was located in RT 02 RW 23 Wonorejo, Karanganyar. The population of the research was premenopausal women of PKK Dahlia members. The research used simple random sampling with 30 women as the samples. The data was collected by questionnaire and observation sheet. Data analysis was carried out computerized using the SPSS 20.0 program with Chi-Square statistical test.Results: There were 66,7% (20 respondents) that have high knowledge about facing menopause and there were 60% (18 respondents) that ready to face menopause. The statistic test using chi-square resulted in p-value = 0.045 (p<0.05), which means there was a correlation of the knowledge about menopause with the readiness ahead of menopause for premenopausal women.Conclusion: There was a correlation of the knowledge about menopause with the readiness of menopause for premenopausal women.